2005
DOI: 10.1038/sj.npp.1300717
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Alterations in c-fos and Egr-1 (zif268) Expression Throughout the Rat Brain Following Acute Administration of Different Classes of Antidepressant Compounds

Abstract: The majority of immediate-early gene (IEG) studies focus on a few key brain regions associated with the class of psychoactive compound being studied. Recently, using a meta-analysis of the c-fos literature, we demonstrated the utility of c-fos profiling to classify such compounds. The present study examined acute delivery of a range of antidepressant classes; fluoxetine, imipramine, LiCl, and mirtazapine. The dual aims were to study the IEG profiles of these varying classes of antidepressants throughout the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 40 publications
2
30
1
2
Order By: Relevance
“…Essentially all studies were conducted after acute (30 min-2 h) administration of antidepressants. A reasonably consistent observation is that administration of pharmacologically diverse antidepressants (SSRIs, selective NRIs, MAOIs, mirtazapine) increase c-fos or c-Fos in the central nucleus of the amygdala (CeA) and BNST (Beck, 1995;Duncan et al, 1996;Fraga et al, 2005;Miyata et al, 2005;Morelli et al, 1999;Slattery et al, 2005;Sumner et al, 2004;Thomsen and Helboe, 2003). This increase was also seen in female rats treated acutely with fluoxetine (Torres et al, 1998).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Essentially all studies were conducted after acute (30 min-2 h) administration of antidepressants. A reasonably consistent observation is that administration of pharmacologically diverse antidepressants (SSRIs, selective NRIs, MAOIs, mirtazapine) increase c-fos or c-Fos in the central nucleus of the amygdala (CeA) and BNST (Beck, 1995;Duncan et al, 1996;Fraga et al, 2005;Miyata et al, 2005;Morelli et al, 1999;Slattery et al, 2005;Sumner et al, 2004;Thomsen and Helboe, 2003). This increase was also seen in female rats treated acutely with fluoxetine (Torres et al, 1998).…”
Section: Discussionmentioning
confidence: 83%
“…Most studies report no increase in the DRN, although Fraga et al (2005) did find an increase after administration of fluoxetine. When increases in the LC have been reported, it has been upon administration of the SSRI fluoxetine (Fraga et al, 2005;Slattery et al, 2005;Sumner et al, 2004) but, with one exception (Beck, 1995), not with other types of antidepressants. In general, increases have not been reported in the hippocampus and many other regions of brain and effects in cortical areas have been quite inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Somewhat surprisingly, administration of fluoxetine (Fraga et al, 2005;Slattery et al, 2005) but not other types of antidepressants, with one exception (Ková cs, 1998), was found to increase c-Fos in the LC. In general, increases have not been reported in the DRN although Fraga et al (2005) found an increase after short-term administration of fluoxetine.…”
Section: Downloaded Frommentioning
confidence: 96%
“…In general, increases have not been reported in the DRN although Fraga et al (2005) found an increase after short-term administration of fluoxetine. Most studies show increases in c-fos or c-Fos in the CeA and BNST after short-term administration of different classes of antidepressants (Beck, 1995;Fraga et al, 2005;Slattery et al, 2005;Bechtholt et al, 2008). Longterm treatment of rats with either paroxetine (Muigg et al, 2007) or citalopram (Kuipers et al, 2006) did not increase c-Fos in any brain region examined, including the CeA.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation